A new occupational and environmental hazard - nanoplastic - Michał Rakowski; Agnieszka Grzelak (Nofer Institute of Occupational Medicine, 2020)
Problems arising from the accumulation of plastic waste in the environment have become global. Appeals to stop the usage of disposable drinking straws or plastic cutlery did not come out without reason - 320 million tons of plastic products are produced annually, of which 40% are disposable items. More and more countries and private enterprises are giving up these types of items in favor of their biodegradable substitutes, e.g., cardboard drinking straws. Plastic waste in the environment is subject to a number of physicochemical interactions and biodegradation in which bacteria are involved. By using synthetic waste, they reduce the size of plastic garbage while increasing its dispersion in the environment. Small plastic particles, invisible to the naked eye, are called nanoplastic. Nanoplastic is not inert to living organisms. Due to its size, it is taken up with food by animals and passed on in the trophic chain. The ability to penetrate the body's barriers through nanoplastic leads to the induction of biological effects with various outcomes. Research studies on the interaction of nanoplastic with living organisms are carried out in many laboratories; however, their number is still a drop in the ocean of the data needed to draw clear-cut conclusions about the impact of nanoplastic on living organisms. There is also no data on the direct exposure to nanoplastic contamination at workplaces, schools and public utilities, standards describing the acceptable concentration of nanoplastic in food products and drinking water, and in vitro tests on nanoparticles other than polystyrene nanoparticles. Complementing the existing data will allow assessing the risks arising from the exposure of organisms to nanoplastic. Med Pr. 2020;71(6):743-56